Advanced Glycation End Products Enhance Biofilm Formation by Promoting Extracellular DNA Release Through sigB Upregulation in Staphylococcus aureus - Xie, Xiaoying; Liu, Xiaoqiang; Li, Yanling; Luo, Ling; Yuan, Wenchang; Chen, Baiji; Liang, Guoyan; Shen, Rui; Li, Hongyu; Huang, Songyin; Duan, Chaohui (Frontiers in Microbiology, 2020)
Bacterial biofilms do serious harm to the diabetic foot ulcer (DFU) because they play a crucial role in infection invasion and spread. Staphylococcus aureus, the predominant Gram-positive bacteria in diabetic foot infection (DFI), is often associated with colonization and biofilm formation. Through biofilm formation tests in vitro, we observed that S. aureus bacteria isolated from DFU wounds were more prone to form biofilms than those from non-diabetic patients, while there was no difference in blood sugar between the biofilm (+) diabetics (DB+) and biofilm (-) diabetics (DB-). Furthermore, we found that advanced glycation end products (AGEs) promoted the biofilm formation of S. aureus in clinical isolates and laboratory strains in vitro, including a methicillin-resistant strain. Analysis of biofilm components demonstrated that the biofilms formed mainly by increasing extracellular DNA (eDNA) release; remarkably, the S. aureus global regulator sigB was upregulated, and its downstream factor lrgA was downregulated after AGE treatments. Mechanism studies using a sigB-deleted mutant (Newman-ΔsigB) confirmed that AGEs decreased expression of lrgA via induction of sigB, which is responsible for eDNA release and is a required component for S. aureus biofilm development. In conclusion, the present study suggests that AGEs promote S. aureus biofilm formation via an eDNA-dependent pathway by regulating sigB. The data generated by this study will provide experimental proof and theoretical support to improve DFU infection healing.